Analisis Edukatif Kebijakan Suku Bunga Bank Indonesia Berdasarkan Taylor Rule (2022–2023) - Mutia Rafa Nursawitri; Nadia Sulistyaningsih; Miranda Herdia Nova; Miftahul Jannah; Khanaya Isyabrina Maryam; Gregorius Agung Steven Simanjuntak; Ahmad Setiawan Nuraya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes Bank Indonesia’s benchmark interest rate policy during the 2022–2023 period using the Taylor Rule approach, a simple formula that links interest rate settings with inflation conditions and the output gap. The research adopts a descriptive quantitative method. The purpose of this study is to provide a more comprehensive understanding for the general public regarding the fundamentals behind Bank Indonesia’s interest rate decisions. The data used were obtained from Bank Indonesia and Statistics Indonesia (Badan Pusat Statistik), including actual inflation and economic growth figures. The analysis results indicate that in several periods, Bank Indonesia’s decisions aligned with the Taylor Rule, particularly in the second half of 2022 when core inflation exceeded the central bank’s target. However, some deviations were observed, primarily due to external economic shocks and currency volatility considerations. The study concludes that although the Taylor Rule can serve as an initial guideline, Bank Indonesia must remain flexible in responding to economic challenges. This research is expected to enhance public understanding of how interest rate policies are formulated in Indonesia.